Evaluating Finansial Due Diligence in the Strategic Acquisition of PT Suryamas Dutamakmur, Tbk (SMDM) by PT Bumi Serpong Damai, Tbk (SMDM) - Griselda Daulay, Elvina; Arif Sumirat, Erman (Journal of Accounting and Finance Management, 2025)
This research evaluates the strategic acquisition of PT Suryamas Dutamakmur Tbk. (SMDM) by PT Bumi Serpong Damai Tbk. (BSDE) within Indonesia's competitive real estate market. The study focuses on analyzing SMDM's financial performance, determining its valuation, and quantifying the synergies arising from the acquisition. Using financial analysis, discounted cash flow (DCF), relative valuation, and Damodaran’s synergy valuation framework, the study examines the financial and operational aspects of the transaction. Results indicate that SMDM's fluctuating financial performance, highlighted by its strong working capital management and asset turnover, complements BSDE's broader portfolio and profitability metrics. Synergy valuation suggests an additional value of Rp3.483 trillion, exceeding the acquisition cost of Rp2.36 trillion, reinforcing the transaction's financial feasibility. This synergy arises from operational efficiencies, portfolio diversification, and enhanced financial stability, including a reduced cost of capital at 12.05%. Macroeconomic conditions, such as declining interest rates and supportive fiscal policies, present favorable opportunities for the real estate sector while highlighting challenges such as high competition and fluctuating market demand. The findings emphasize the need for strategic integration, leveraging shared resources, and aligning operational strategies to maximize long-term value creation for stakeholders.